A development process for extending buildings vertically – based on a case study of four extended buildings. Issue 3 (14th May 2019) - Sundling, Rikard
Abstract : Purpose: The purpose of the study, upon which this paper is based, was to contribute an improved understanding of the vertical extension of buildings, by presenting a development process for its implementation in which the key aspects to consider when planning such extensions are highlighted. Design/methodology/approach: The approach is based on linking the diffusion of innovation together with case study research to stimulate further development in vertically extending buildings. Four cases of vertically extended buildings in Sweden were selected for the study. Findings: The development process highlights seven key areas for decisions when planning a vertical extension. These areas are: opportunities for vertical extension; strategies for implementation; detailed planning process; concept development; evaluation; building permit; and procurement. The development processes and lessons learnt from each case are presented, covering both success and failure. Research limitations/implications: The research is based on four cases of vertically extended buildings. The findings offer valuable insights into the development process which should provide the research community with an improved understanding of the challenges faced. Practical implications: The findings will help planners, housing owners, housing developers and facility managers better understand the conditions that favour successful implementation of vertical extensions. Originality/value: The paper provides the reader with an understanding of the challenges faced in the vertical extension of a building and the means of overcoming them to create a simplified development process.